Hepatorenal syndrome in cirrhotic patients in Madagascar: epidemiology, clinical profile and in-hospital outcomes - Razafindrazoto , Chantelli Iamblaudiot; Rakotozafindrabe, Rina; Rabenjanahary , Tovo (African Journal of Nephrology, 2021)
Background: Hepatorenal syndrome (HRS) is a frequent and serious complication in decompensated cirrhosis. The objective of this study was to describe the epidemiology, clinical profiles and outcomes of hepatorenal syndrome (HRS). Methods: This was a retrospective and descriptive study over a period of 75 months, from January 2011 to March 2017, carried out at the Gastroenterology Unit, University Hospital Joseph Raseta Befelatanana, Antananarivo, Madagascar. Results: The hospital prevalence of decompensated cirrhosis with HRS was 7.9% (41/519). The mean age of the patients was 49.8 ± 11.33 years (range 25–70 years). Male gender predominated at 83% (n = 34). History of alcohol (46.3%) and viral hepatitis B (34.1%) were the main aetiologies of cirrhotic disease. Most of our patients (88%) had a Child-Pugh C score. HRS occurred during the first decompensation (63.4%) and the first years of cirrhosis (81%). Spontaneous bacterial peritonitis (46%) and gastrointestinal bleeding (32%) were the main risk factors. HRS type-1 predominated at 66% (n = 27). The prognosis was poor with a mortality rate of 81% (100% in HRS type 1 and 42.9% in type 2). Most patients (n = 22; 67%) died within 14 days. Conclusion: The prevalence of HRS was 7.9%. It affects young people with advanced cirrhosis. The prognosis is grim with a mortality rate of 81%. Keywords: Acute kidney injury, liver cirrhosis, hepatorenal syndrome, Madagascar